Pembelajaran Ekonomi Berjatidiri Bangsa - Rahmatullah, Rahmatullah (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2018)
This paper is the result of research that aims to internalize the economic values of the nation in accordance with the economic basis of the nation, namely Pancasila and Article 33 of the 1945 Constitution. This is important to be realized in order to realize the generation of the nation that has the understanding, attitude and economic behavior in accordance with economic principles of the nation. The method used refers to the Dick & Carey model, and the product trial is done by Class Action Research approach. The results showed that the learning of the nation's national identity is very effective in applied in the learning process although it is a supplement